The phenomenology of stress and coping among heads-of-department in secondary schools - Ong, Enid Ah Geok. (2009)
This study examined the relationships of stress with school-situated and family factors among a sample of department heads in secondary schools in Singapore. The six school-situated factors selected for study were: role conflict, role ambiguity, collegiality, time pressure, leadership, and nature of job. Two family factors, namely, family relationships and family commitments were also included